Más allá de la visión: innovación y e-commerce en el sector óptico de Lima - Rojas Plasencia, Karina Milagros (2025)
This study examines the adoption of administrative and technological innovations in Lima’s optical sector through a descriptive qualitative approach, based on semi-structured interviews and analysis using ATLAS. ti. The findings reveal progress in organizational management, driven by strategic planning, clear structures, and participatory leadership, as well as the use of technologies to monitor productivity. On the technological front, continuous training, personalization and diagnostic tools, process automation, and the integration of ICTs stand out as means to enhance customer service. However, economic and technical barriers -such as high investment costs and uncertainty about results- continue to hinder full digital transformation. In summary, the study provides evidence of how optical businesses in Lima are incorporating innovations to strengthen their competitiveness, operational efficiency, and customer experience, while also identifying the key challenges that still limit their modernization.